Manajemen Pemasaran Pendidikan di Madrasah Tsanawiyah Ma’had Al-Zaytun Indramayu - Yana Sutiana; Turi Turiah; Sri Lestari; Titi Sujati (UniSadhuGuna Business School, 2023)
Marketing is a process whereby a person or group can fulfill desires through efforts to influence, distribute, and transfer ownership from one person to another or between groups, both in terms of goods or services. The marketing carried out by Madrasah Tsanawiyah Ma'had Al-Zaytun has been quite good in introducing schools with a good image in the eyes of the public and also the quality of teachers who are quite good in implementing a learning system for students. This is what attracts public interest in Madrasah Tsanawiyah Ma'had Al-Zaytun. Apart from that, the strategic geographical location which is in the Sandrem Block of Mekarjaya Village, Kec. Switch Kab. Indramayu and adequate facilities as one of the bargaining values of educational marketing. So that the number of enthusiasts from year to year is increasing. The aim of this research is to find out the educational marketing management at MTs Ma'had Al-Zaytun. The method used is a qualitative research method. Data collection techniques used in this study were observation, interviews and documentation. The data analysis technique used to analyze the data is an interactive model data analysis including data reduction, data presentation and conclusions. the results of the study that educational marketing management at MTsS Ma'had Al-Zaytun are; 1) determining the target market 2) placing members of the foundation in every province in Indonesia and abroad. 3) in collaboration with alumni of Ma'had Al-zaytun, 4) using digital media.